Causes, clinical presentation, management, and outcomes of chronic subdural hematoma at Mbarara Regional Referral Hospital - Kitya, David; Punchak, Maria; Abdelgadir, Jihad; Obiga, Oscar; Harborne, Derek; Haglund, Michael M (Neurosurg Focus, 2018)
OBJECTIVE Causes, clinical presentation, management, and outcomes of chronic subdural hematoma (CSDH) in low- and middle-income countries are not well characterized in the literature. Knowledge regarding these factors would be beneficial in the development and implementation of effective preventive and management measures for affected patients. The authors conducted a study to gain a better understanding of these factors in a low-income setting. METHODS This prospective study was performed at Mbarara Regional Referral Hospital (MRRH) in Uganda between January 2014 and June 2017. Patients of any age who presented and were diagnosed with CSDH during the aforemen tioned time period were included in the study. Variables were collected from patients’ files at discharge and follow-up clinic visits. The primary outcome of interest was death. Secondary outcomes of interest included discharge Glasgow Coma Scale (GCS) score, ICU admission, wound infection, and CSDH recurrence. RESULTS Two hundred five patients, the majority of whom were male (147 [72.8%]), were enrolled in the study. The mean patient age was 60.2 years (SD 17.7). Most CSDHs occurred as a result of motor vehicle collisions (MVCs) and falls, 35.6% (73/205) and 24.9% (51/205), respectively. The sex ratio and mean age varied depending on the mechanism of injury. Headache was the most common presenting symptom (89.6%, 173/193), whereas seizures were uncommon (11.5%, 23/200). Presenting symptoms differed by age. A total of 202 patients underwent surgical intervention with burr holes and drainage, and 22.8% (46) were admitted to the ICU. Two patients suffered a recurrence, 5 developed a post-operative wound infection, and 18 died. Admission GCS score was a significant predictor of the discharge GCS score (p = 0.004), ICU admission (p < 0.001), and death (p < 0.001). CONCLUSIONS Trauma from an MVC is the commonest cause of CSDH among the young. For the elderly, falling is common, but the majority has CSDH with no known cause. Although the clinical presentation is broad, there are several pronounced differences based on age. Burr hole surgery plus drainage is a safe and reliable intervention. A low preoperative GCS score is a risk factor for ICU admission and death.
Keywords: Chronic subdural hematoma; Low- and middle-income countries; Neurosurgical access